Application of Artificial Intelligence Technology in Virtual Reality Animation Aided Production. Issue 3 (February 2021) - Yang, Yixuan
Abstract: The three-dimensional animation developed by virtual reality technology has been widely concerned. Although the virtual reality technology has changed the traditional animation production mode to a great extent, the existing virtual reality technology is still not perfect, which needs to be further compensated by artificial intelligence technology, and the domestic research on this aspect is less. Therefore, this paper establishes the application of artificial intelligence technology in virtual reality aided animation production. This paper investigates the popularity of artificial intelligence technology course in animation major of colleges and universities, and thinks that the interdisciplinary education needs to be strengthened. In this paper, the application of artificial intelligence technology in virtual reality aided animation production is analyzed in detail. Firstly, it is considered that artificial intelligence makes animation tools intelligent and further changes the traditional animation production mode. Secondly, the importance of artificial intelligence technology in 3D animation modelling due to the current that virtual reality technology is not perfect. It needs to be improved through artificial intelligence technology. Finally, this paper analyzes the development trend of the integration of artificial intelligence and virtual reality. This paper believes that the intelligent artistic creation is the future development trend, and the efficiency and effect of animation production can be effectively improved through artificial intelligence technology.